A aurora da experiência democrática no município de João Pessoa-PB: poder local, câmara municipal e participação política (1945-1951) - Silva, Carla Schayane Costa (2020)
This dissertation is inserted in the research line "History and Regionalities" and seeks to understand the establishment of democratic experience (1945-1964) in the municipality of João Pessoa-PB from the analysis of the exercise of local power and political participation of the City Council in the Municipality of Joao Pessoa between 1947 and 1951. For this, we discussed the process of the fall of the dictatorship of the New State (1937 - 1945) and the resumption of the political life of the country from the organization of political parties and the electoral process. Understanding the process of redemocratization in order to reflect on the exercise of local democracy, we studied the political aspects of the capital of Paraiba from the actions of the councilors who composed the first legislature of the City of João Pessoa and the participation of local workers in the political process of then. From the historiographical point of view, this research is placed in the field of the New Political History, from which we use the concept of Political Culture (MOTTA, 2009) seeking to understand the exercise of local power. In methodological terms, in addition to a broad bibliographic review, we work with the minutes of the City Council of João Pessoa, the quantitative data of the electronic archives of the Regional Electoral Court of Paraíba (TRE-PB) and some newspapers in circulation at the time. Through the historiographical debates, the conceptual discussions and the analysis of the expressive corpus of documents, we seek to establish a framework of the political process of the municipality and new possibilities of understanding the policy of the capital of Paraiba during the time of the democratic experience.